(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Among the pests of pistachio orchards in Greece - Agonoscena pistaciae Burck. & Laut., A. cisti (Puton), A. targionii (Licht.) and Megagonoscena gallicola (Burck. & Laut.) - the first is economically the most important. A. pistaciae appears on the leaves of pistachio from mid April and remains during the whole growing season until the fall of the leaves at the end of November. From mid August onwards the population density increases rapidly causing severe problems in this culture. A. cisti appears at the same time as the above mentioned one and remains on the pistachio leaves in small to medium sized populations until the end of July while, in small numbers too, M. gallicola is observed from mid July until the end of August. Finally, in the Avlona area (Attica) A. targionii was found in one sample only. At the beginning of May the presence of Chrysoperla carnea Steph. and Anthocoris nemoralis F. and of the parasitoid Psyllaephagus pistaciae Ferriere is woteworthy. They are found in satisfactory numbers between the beginning of August and mid-November and play a part in reducing the populations of A. pistaciae that is on the point of hibernating.